Smoking Status on Outcomes After Percutaneous Coronary Intervention - Chen, Tao (Clin Cardiol, 2012)
BACKGROUND: The effect of smoking on prognosis among patients undergoing percutaneous coronary intervention (PCI) is controversial, and data on the importance of smoking cessation or reductions were lacking. HYPOTHESIS: Smoking cessation or reductions could reduce the risk of adverse outcomes in patient after PCI. METHODS: There were 19 506 consecutive patients who had undergone successful PCI between April 2004 and January 2010 followed. Extensive data, including self‐reported smoking habits, were obtained at baseline and during follow‐up. RESULTS: Compared with post‐PCI quitters and persistent smokers, the nonsmokers and pre‐PCI quitters were older and had a higher prevalence of comorbid factors such as hypertension and impaired left ventricle function. The adjusted hazard ratios for mortality were 2.52 (95% confidence interval [CI]: 1.92–3.30) for nonsmokers, 0.52 (95% CI: 0.32–0.84) for pre‐PCI quitters, and 0.11 (95% CI: 0.06–0.22) for post‐PCI quitters, compared to persistent smokers. With respect to additional revascularizations, a higher risk was observed among the quitters (1.70 [95% CI: 1.40–2.08] for pre‐PCI quitters and 1.59 [95% CI: 1.36–1.85] for post‐PCI quitters) as well as the nonsmokers (1.40 [95% CI: 1.20–1.64]). Among persistent smokers, each reduction of 5 cigarettes/day was associated with a 72% decline in mortality risk (P < 0.001) but did not reach statistical significant for repeated revascularizations (0.80 [95% CI: 0.46–1.37], P = 0.4132). CONCLUSIONS: Despite a higher risk of revascularization, the cessation of smoking either before or after PCI is beneficial in all‐cause mortality. The apparent smoker's paradox may be explained by the differences in baseline risk or the reduced sensitivity to adverse outcomes as well as the reluctance to seek medical help among smokers. This study received an unrestricted grant from Pfizer Investment Co., China. The authors have no other funding, financial relationships, or conflicts of interest to disclose.